A temperature-dependent potential model for mercury in the description of vapour-liquid equilibrium & adsorption in activated carbon - Liu, X.; Fan, Chunyan; Do, D.D.; Pareek, Vishnu; Yang, P. (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
© 2019 Elsevier Ltd A practical potential equation for mercury was developed, by incorporating the long-ranged interaction and multi-body effects into the temperature-dependent dispersion parameters, to describe the thermodynamic properties of the liquid-vapour equilibrium and adsorption in carbonaceous materials. The collision diameter (σ) decreases and the well depth of interaction energy (ε) increases with temperature, with the product σ6ε (a measure of attraction) decreasing with temperature. The critical temperature derived from this model, 1745 K, agrees well with the experimental value of 1751 K, and the wetting temperature of mercury on graphite was found to be 1600 K, supporting the fact that mercury does not wet carbon under ambient conditions. Furthermore, it was illustrated with mercury can fill ultrafine graphitic slit pores, whose widths less than 0.7 nm, under ambient temperatures, because of the enhancement of the solid-fluid potential and the strong intermolecular interactions, and the simulation results qualitatively agree well with experimental data.